A Study of Methods and Techniques to Manage the Occupational Stress Among the Bank Employees of Meerut Region - Agarwal, Himanshu; Rastogi, Nitin Kumar (Journal of Commerce and Trade, 2018)
Stress on individuals ranges from personal day-to-day life to their organizational activities. Stress is the spice of life and the absence of stress makes life dull, monotonous and spiritless. Workplace stress has been shown to have a detrimental effect on the health and wellbeing of employees, as well as a negative impact on workplace productivity and profits. Stress may cause within organizational context and outside. The job nature of banking employees is very tedious as it involves the direct customer interaction in all levels. There are several self-help remedies which are used to produce effective techniques for coping with stress. So it should be considered an efficient way of improving organizational profitability and reducing costs through lowering rates of absenteeism and turnover. Because employees spend roughly one third of their lives working in an organization, the sound mental health of employees is of paramount importance. The management takes necessary initiatives to overcome the disastrous effect of occupational stress. Managing stress will improve the chances of achieving sustainable productivity levels. Stress management should be included as one of the top agendas in modern day society. Classification-JEL : G21, J24, J81.